2015
DOI: 10.1111/clr.12693
|View full text |Cite
|
Sign up to set email alerts
|

Success rate of short dental implants supporting single crowns and fixed bridges

Abstract: Based on this preliminary data, we conclude that rough surface design short dental implants (6 and 8 mm in length) have similar success rate when compared to 11-mm implants. Long-term data with larger number of implants and subjects are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 29 publications
2
29
1
2
Order By: Relevance
“…This bone level change corroborates well with previously published data for the OsseoSpeed implant, short implants 21,22,29,[31][32][33][34]37,[39][40][41] as well as for standard length implants. 15,16,[42][43][44][45] In this study, 4 early implant failures occurred and one implant rotated at 5 weeks post-surgery.…”
Section: Discussionsupporting
confidence: 92%
“…This bone level change corroborates well with previously published data for the OsseoSpeed implant, short implants 21,22,29,[31][32][33][34]37,[39][40][41] as well as for standard length implants. 15,16,[42][43][44][45] In this study, 4 early implant failures occurred and one implant rotated at 5 weeks post-surgery.…”
Section: Discussionsupporting
confidence: 92%
“…This practice may be due to the suspectable C/I ratio, which might cause poor stress transmission. 32 Published research, including in vitro experiments and clinical studies, suggested that short implants splinted together by crowns deployed the occlusal force evenly, leading to a better result. 33,34 The primary consequence involved in the inappropriate design of restoration was MBL, which increased the risk of peri-implantitis or even the loss of short implants.…”
Section: Discussionmentioning
confidence: 99%
“…All implants (OsseoSpeed, DENTSPLY Implants, Waltham, MA, USA) were 4 mm in diameter. Depending upon their length, implants were classified as either short implants (6-8 mm in length) or long implants (11 mm in length) (Malmstrom et al 2015). Full-thickness mucoperiosteal flaps were raised under local anesthesia using a no.…”
Section: Surgical Protocol and Implant-related Characteristicsmentioning
confidence: 99%